Losing the Center : The Decline of American Liberalism, 1968-1992 - Bloodworth, Jeffrey (Book collections on Project MUSE., 2013)
Many Americans consider John F. Kennedy's presidency to represent the apex of American liberalism. Kennedy's ""Vital Center"" blueprint united middle-class and working-class Democrats and promoted freedom abroad while recognizing the limits of American power. Liberalism thrived in the early 1960s, but its heyday was short-lived. In Losing the Center, Jeffrey Bloodworth demonstrates how and why the once-dominant ideology began its steep decline, exploring its failures through the biographies of some of the Democratic Party's most important leaders, including Daniel Patrick Moynihan, He